Judicial Inconsistency and Its Implications for Trademark Protection in Indonesia - Purba, Jeremy Exaudi; Silalahi, Wilma (Jurnal Ilmu Hukum Kyadiren, 2026)
The issue of legal certainty and trademark protection for relevant parties arises from the inconsistency between the decisions of the Judex Facti and Judex Juris in trademark cancellation cases. This study aims to identify the nature of this inconsistency and its implications for trademark legal protection in Indonesia. Drawing on statutory regulations, Medan Commercial Court Decision No. 6/Pdt.Sus-HKI/Merek/2022, and Supreme Court Decision No. 989 K/Pdt.Sus-HKI/2024, this normative legal research employs both case-based and conceptual approaches. The findings indicate that the Commercial Court adopts a narrow interpretation of “interested parties” and does not recognize first use as a legal basis, resulting in the dismissal of the trademark cancellation claim. In contrast, the Supreme Court applies a broader and more progressive interpretation by acknowledging historical use and identifying indications of bad faith in the trademark registration process. These divergent interpretations generate legal uncertainty, underscoring the need for harmonization between courts to ensure equitable trademark protection.